The bounded solutions to nonlinear fifth-order differential equations with delay - Tunç,Cemil (2009)
In this paper, we improve some boundedness results, which have been obtained with respect to nonlinear differential equations of fifth order without delay, to a certain functional differential equation with constant delay. We give an illustrative example and also verify our main result by means of Liaponov tecnique.